The use of fuzzy logic for the automation of the operation of irrigation systems - Лєві, Л. І. (Scientific Progress & Innovations, 2018)
The highest yield of agricultural crops is achieved with the optimal amount of moisture, nutrition, heat, air and light. In this case, the necessary water regime for agricultural crops is created by the appropriate irrigation regime, which establishes the norms, timing and number of irrigation, depending on the biological characteristics of crops, natural and economic conditions. In determining the flow of water to irrigation take into account water consumption or total evaporation, which depends on climatic conditions, the amount of thermal energy that enters the surface, soil moisture, species and yield of the crop. Therefore, the issues of adaptation and self-studying of automated systems for controlling soil moisture in the conditions of the action of random weather factors, changes in the characteristics of the control object, improving the accuracy of control due to the operational consideration of the perturbations of the object, ensuring the receipt of planned yields of agricultural crops for the rational use of energy and water resources. In addition, modern water management systems for crops should not only provide sufficient management accuracy, but also forecast the need for plants in water for a certain period, minimize energy and water costs without loss of crop, be reliable and easy to operate, provide the operator with complete and timely information the value of all parameters and the state of the control system. A comprehensive solution to these problems is possible only through the development of modern technical means of automation, new mathematical models of moisture transfer in the unsaturated zone of soil and methods of managing moisture content of agricultural crops. Thus, the development of methods for automated management of moisture content of agricultural crops, taking into account perturbations, is an actual scientific and practical task. To solve these problems, the approach to automating the management of irrigation systems with the use of fuzzy logic is considered. The power and intuitive simplicity of fuzzy logic as a solution to problems ensures its successful application in information monitoring and analysis systems. At the same time there is a connection of human intuition and operator experience. The offered approach allows to improve the accuracy of soil moisture management, to ensure that planned crops are harvested, and to save water and energy resources at the expense of their rational use.